Building and communicating territorial brand values: The case of Destination British Columbia - Cristofol, Francisco Javier; Zamarreño-Aramendia, Gorka; Cruz-Ruiz, Elena de los Reyes; San Egenio-Vela, Jordi de (My University, 2024)
In today’s interconnected world, efectively communicating territorial values is paramount for regions seeking to distinguish themselves globally. Efective destination branding requires carefully synthesizing cultural, historical, natural, and socioeconomic elements to create an enticing identity for tourists, investors, and locals. How a region communicates its unique attributes is crucial in shaping its perception and attractiveness in a highly competitive global market. British Columbia is a prime example of successful destination branding, thanks to its remarkable cultural diversity and breathtaking natural landscapes. BC has efectively conveyed its values and appeal to a worldwide audience through various innovative strategies and platforms. This paper explores BC’s communication eforts through its website and social media, analyzing how it conveys its essence to a diverse audience and positions itself on the world stage. Ultimately, BC’s success in this domain highlights the critical role of efective territorial value communication in today’s globalized world.
Keywords: Turismo - Marketing; British Columbia; Place Branding